Thermal properties characteristics of MWCNT-OH based Nanofluids in mixture of Ethylene Glycol and Deionized water / Amirah Abdullah...[et al.] - Abdullah*,, Amirah; Mohamad,, Imran Syakir; Masripan,, Nor Azmmi; Zainal Abidin, Syazwani; Bani Hashim, Ahmad Yusairi (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Conventional fluids have lower thermal properties. Moreover, the low freezing and high boiling point of water are another issues have made limitation occurred. Therefore, inclusion of MWCNT-OH nanoparticles in mixture of ethylene glycol and deionized water is an alternative way to solve these problems. Then, two-step method is used in nanofluids synthesizing through homogenized and sonicated all materials together such as MWCNT-OH nanoparticles (0.1 wt% to 1.0 wt%) and PVP surfactant (0.01 wt%) in mixture of ethylene glycol to deionized water (20:80) for five minutes. The nanofluids were tested in thermal conductivity test, heat transfer coefficient test and specific heat test. Thus, the thermal conductivity results show positive enhancement for all concentrations and 0.9 wt% of MWCNT-OH based nanofluids have the highest thermal conductivity. It is followed by 0.3 wt% and 0.6 wt% of MWCNT-OH based nanofluids. The percentage enhancement of thermal conductivity is about 0.812% to 17.0%. Whilst, high heat transfer coefficient has given increment of nanofluids Nusselt number. However, specific heat test have decrement values with increment of weight loading even though has high thermal conductivity values. This thermal properties results are affected by dispersion and suspensions of nanoparticles possess higher thermal conductivity. In addition, functionalized group attached on nanoparticles, quantity of surfactant, ultrasonication process and nanofluids stability are factors which influenced the thermal conductivity. Moreover, heat absorption and capacity of nanofluids and as well as temperature are another factors that capable to enhance the thermal conductivity. The small size and high surface area of nanoparticles, low surface roughness, nanoparticles concentration, temperature and nanoparticles interaction are others influenced factors in these test. Whilst, lower specific heat value on nanoparticles and agglomeration form affected in specific heat test. In conclusion, addition of MWCNT-OH nanoparticles in mixture of base fluids is capable to improve thermal properties of nanofluids.